Patients with in‐transit melanoma metastases have comparable survival outcomes following isolated limb infusion or intralesional PV‐10—A propensity score matched, single center study. Issue 6 (15th January 2019) - Read, Tavis; Fayers, Warren; Thomas, Janine; Wagels, Michael; Barbour, Andrew; Mark Smithers, B.
Abstract : Background and Objective: Isolated limb infusion (ILI) and intralesional PV‐10 are well described locoregional therapies for in‐transit melanoma. The objective of this study was to assess the effect of these treatments on survival outcomes within a cohort matched for key characteristics. Methods: Patients were treated using ILI or intralesional PV‐10 at a single institution and the data prospectively recorded. Propensity score matching was performed using key covariates within a logistic regression model. The primary outcome was the melanoma‐specific survival. Results: Seventy‐two patients nonrandomized were successfully matched. Both treatments produced similar best overall responses. The median melanoma‐specific survival (MSS) was 74.4 months from ILI and 36.4 months from PV‐10 treatments ( P  = 0.164). Within the ILI subgroup, the 12‐, 24‐, 36‐ and 60‐month MSS rates were 85.3%, 75.3%, 60.1%, and 60.1%, respectively. From the time of PV‐10 the corresponding 12‐, 24‐, 36‐, and 60‐month MSS rates were 82.6%, 70.0%, 53.9%, and 35.9%. On multivariate analysis, there was a significant difference in survival comparing completely with noncomplete responders ( P  = 0.031). Conclusions: These findings demonstrate that ILI and PV‐10 treatments for in‐transit disease produce comparable long‐term survival. Both therapies have reproducible response rates and predominantly localized and tolerable side‐effects.